Influência da música na atividade motora de crianças nascidasprematuras e com peso inferior a 1500 g - Daniel da Costa Campos (2008)
This research aimed to verify the influence of music in the motor behavior of premature children (under thirty four weeks of pregnancy), and weight under 1500 grams. Nine premature children (experimental group) and nine term birth children, without any perinatal intercurrence (control group), both between three and four years old, were studied. The research was structured in three different moments: (1) under sound stimuli of a relaxing music piece; (2) under sound stimuli of excitingmusic piece and (3) with no sound stimuli. The second part of the research consisted of a quantitative analyses of the spontaneous non intentional movements of the children (those not related with playing itself) and of a statistical analyses of the data raided througt Kruskal-Wallis and Wilcoxon tests. This analyses showed that (1) thespontaneous non intentional movements observed under exciting music stimuli were significantly different from the ones observed under relaxing music stimuli; (2) the spontaneous non intentional movements observed under relaxing music stimuli; (3) there was no significant difference between the spontaneous non intencional movements observed under exciting music stimuli and the ones observed under nomusic stimuli and (4) there was no significant diference between the spontaneous non intentional movements observed in the experimental group (premature children) and in the control group (term birth children). The results suggest that certain characteristics of music, such as exciting or relaxing, might interfere in the motor behavior of three and four year old children. This work also points out to the necessity of deeper studies about the processes of cortex activation, specially the ones concerning the auditory cortex and the motor control areas.